Pemanfaatan Eco Enzyme Berbasis Air Kelapa dan EM4 untuk Pengelolaan Sampah Rumah Tangga di Perumahan Batara Raya, Batam - Robin, Robin; Onoyi, Nona Jane; Yantri, One; Hangesti, Pangastuti; Fawwaz, Liyana Khairunnisa (Jurnal Pengabdian Masyarakat (ABDIRA), 2025)
Batam City, as one of Indonesia's industrial centers, faces significant challenges in waste management. It is estimated that more than 1,200 tons of waste are produced daily, of which approximately 60% is organic waste that has the potential to be processed into value-added products. Unfortunately, most of this waste ends up in the Telaga Punggur Landfill, which is now nearing maximum capacity. To address this issue, the Community Service program introduced the use of eco-enzymes as a practical and environmentally friendly solution for household waste management and ecosystem balance. Eco-enzymes are multipurpose liquids produced by fermenting household waste (vegetable and fruit scraps) that can be used as liquid fertilizer, floor cleaner, and other products. The manufacturing process uses a mixture of coconut water, molasses, and EM4 as a booster. With this medium, the fermentation time can be shortened to 15 days, compared to using only plain water and molasses, which takes 3 months. This community service activity was carried out in partnership with the Family Welfare Movement (PKK) women of the Batara Raya Housing Complex, Belian Village, Batam, with a focus on outreach, training, and practice. It is hoped that this initiative will reduce the burden on landfills and build collective awareness for responsible waste management and maintaining ecosystem balance. Through sustainable implementation, Batam City is expected to become green, clean, and sustainable.